2011
DOI: 10.1177/0969776410390747
|View full text |Cite
|
Sign up to set email alerts
|

Youth migration, rurality and class

Abstract: Drawing on Bourdieusian social theory, the paper combines class and social constructionist perspectives to reconceptualize youth's rural-to-urban migration. It discusses how structural properties of everyday lives, e.g. class background, inform rural youth's evaluations of rurality, and how these evaluations generate specific rural/urban residential preferences and migration practices. The theoretical discussion is informed by a survey study among rural teenagers in a remote rural region in Norway -the Mountai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 30 publications
(31 reference statements)
1
46
0
6
Order By: Relevance
“…Equally, perceptions of the rural, and indeed place, vary across the life course (Haartsen, Groote, & Huigen, ). It is good for children (idyllic) but not so good for teenagers (dull) (Haartsen & Strijker, ), and rural adolescents express a preference for rural living when they are older (Glendinning et al, ; Rye, ). A rural residence is attractive to families (Kuhmonen et al, ) and those at or around retirement (Lowe & Speakman, ; Stockdale & MacLeod, ).…”
Section: Towards a Conceptual Frameworkmentioning
confidence: 99%
“…Equally, perceptions of the rural, and indeed place, vary across the life course (Haartsen, Groote, & Huigen, ). It is good for children (idyllic) but not so good for teenagers (dull) (Haartsen & Strijker, ), and rural adolescents express a preference for rural living when they are older (Glendinning et al, ; Rye, ). A rural residence is attractive to families (Kuhmonen et al, ) and those at or around retirement (Lowe & Speakman, ; Stockdale & MacLeod, ).…”
Section: Towards a Conceptual Frameworkmentioning
confidence: 99%
“…Based on location theory and supply-demand theory, considering the complicated land market in China and the available databases, representative elements were chosen to analyze the spatially varying effects on residential land price after a series of statistical analyses, including immigrant population [22,[32][33][34], gross domestic product (GDP) [17,35] and investment in residential buildings [36][37][38][39][40]. The economic data are from the China City Statistical Yearbook directly [41].…”
Section: Impact Factorsmentioning
confidence: 99%
“…The study of Rose [32] revealed strong positive correlations between land price and the level of population or population growth rate. Rye [33] indicated that migration decisions of youths in a remote rural region in Norway resulted from individual and free choices but were still structured by their rural class habitus. Saiz [34] also indicated that rents and housing values in US destination cities are pushed up by immigration.…”
Section: Introductionmentioning
confidence: 99%
“…Rye (2011) observes among young adults that rurality is associated with contradictory images (dull vs. idyllic). Traditionally, research has shown that amenities and quality of life dominate in short-distance moves, but more recently their importance has also been highlighted in amenity-led P. Rérat: Migration and post-university transition or lifestyle migration toward rural or mountainous regions (Gosnell and Abrams, 2011).…”
Section: Sensitive Logicmentioning
confidence: 99%